Nonlocal acoustic black hole metastructures: Achieving broadband and low frequency passive vibration attenuation. (15th April 2022) - Nair, Siddharth; Jokar, Mehdi; Semperlotti, Fabio
Abstract: This paper introduces the concept of nonlocal Acoustic Black Hole (ABH) metastructure and explores, via numerical analyzes, the corresponding vibration attenuation performance. Building on the basic concept of ABH metastructure, which is a thin plate waveguide with embedded periodic grids of ABHs, this work explores the feasibility of using intentionally introduced nonlocality to expand the dynamic operating range of the ABH absorbers. The nonlocal design is expressively conceived to address the two-fold objective of lowering the cut-on frequency of an individual ABH and extending the operating frequency range towards the lower part of the frequency spectrum (or, equivalently, towards longer wavelengths). The role of nonlocality on the transient and steady state dynamic response of the periodic metastructure is investigated via a dedicated semi-analytical model. Different nonlocal designs are presented and their dynamic performances are investigated and compared using numerical models. Results show a remarkable ability of the nonlocal metastructure to achieve significant vibration attenuation behavior in the low frequency bandwidth. Highlights: Introduce the concept of intentional nonlocality in ABH metastructures. A semi-analytical methodology is developed to extract nonlocal dynamic properties. The vibration attenuation performance of proposed designs is numerically evaluated. The design approach achieves significant low frequency vibration attenuation. Remarkable control over the width and location of bandgaps at low frequency.